2016
DOI: 10.1371/journal.pone.0165723
|View full text |Cite
|
Sign up to set email alerts
|

Non-Enzymatic Oligomerization of 3’, 5’ Cyclic AMP

Abstract: Recent studies illustrate that short oligonucleotide sequences can be easily produced from nucleotide precursors in a template-free non-enzymatic way under dehydrating conditions, i.e. using essentially dry materials. Here we report that 3’,5’ cyclic AMP may also serve as a substrate of the reaction, which proceeds under moderate conditions yet with a lower efficiency than the previously reported oligomerization of 3’,5’ cyclic GMP. Optimally the oligomerization requires (i) a temperature of 80°C, (ii) a neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 36 publications
(34 reference statements)
1
39
0
Order By: Relevance
“…Another factor whose activity significantly changed (fivefold ↑) was HelD. As reported in Costanzo et al (2016) (and references therein), the cleavage by alkali or formamide leaves the phosphate group of the attacked phosphodiester bond bound at 3 0 , initially in the 2 0 ,3 0 cyclic form (upper band in the band couples). This increased expression may help the cell to compensate for the absence of RNase J1.…”
Section: Effect Of Rhomentioning
confidence: 77%
“…Another factor whose activity significantly changed (fivefold ↑) was HelD. As reported in Costanzo et al (2016) (and references therein), the cleavage by alkali or formamide leaves the phosphate group of the attacked phosphodiester bond bound at 3 0 , initially in the 2 0 ,3 0 cyclic form (upper band in the band couples). This increased expression may help the cell to compensate for the absence of RNase J1.…”
Section: Effect Of Rhomentioning
confidence: 77%
“…In a more recent study, we reported that prolonged heating of dry 3′,5′‐cAMP also yields short oligonucleotide sequences . The covalent nature of the oligomerization products has been confirmed by a variety of analysis methods, such as PAGE,, MALDI‐ToF, MALDI‐ToF/ToF, NMR, and enzymatic analysis …”
Section: Resultsmentioning
confidence: 75%
“…The polymerization of 3′,5′‐cGMP at moderately high (60–80 °C) temperatures in solution (water or formamide) and under dry conditions has been described in detail . In a more recent study, we reported that prolonged heating of dry 3′,5′‐cAMP also yields short oligonucleotide sequences . The covalent nature of the oligomerization products has been confirmed by a variety of analysis methods, such as PAGE,, MALDI‐ToF, MALDI‐ToF/ToF, NMR, and enzymatic analysis …”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations